Chronic alcohol excess is associated with selective but reversible injury to type 2B muscle fibres. Issue 7 (July 1983) - Slavin, G; Martin, F; Ward, P; Levi, J; Peters, T
Abstract : Patients drinking more than 100 g alcohol/day for longer than three years develop atrophy of striated muscle fibres. This predominantly affects type 2B fibres which are dependent on anaerobic glycolytic metabolism. Atrophy of type 1 and type 2A fibres, which in addition use aerobic mitochondrial respiration, only occurs in the most severe cases and then only to a lesser degree. Abstention from alcohol reverses the changes in muscle which slowly return to normal. Selective injury to type 2B fibres indicates that search should be made for an alcohol-induced biochemical lesion affecting the anaerobic glycolytic pathways of the muscle fibre.